2004
DOI: 10.1023/b:brea.0000025419.26423.b8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in uridine diphospho-glucuronosyltransferase 1A1 (UGT1A1) and risk of breast cancer

Abstract: Uridine diphospho-glucuronosyltransferase 1A1 (UGT1A1) is involved in catalyzing estrogen, the hormone that plays a central role in the etiology of breast cancer. A common polymorphism [A(TA)6TAA (allele *1) to A(TA)7TAA change (allele *28)] in the TATA-box of the promoter region of the UGT1A1 gene has been reported to be associated with a reduced transcription of this gene. We investigated the association of this polymorphism with the risk of breast cancer among 1047 breast cancer cases and 1083 community con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 18 publications
0
46
2
Order By: Relevance
“…We found the distribution of TA repeat genotypes was significantly different between cases and controls, but the patterns were not systematic in the overall analysis. In contrast to the two previous studies conducted in African Americans [4] and in Chinese [8], which found that 7 or 8 allele-containing genotypes were associated with elevated risk of breast cancer in premenopausal women [4] or women younger than 40 years [8], we found that these low activity 7 or 8 allele-containing genotypes were associated with decreased risk of breast cancer among premenopausal women or those younger than 45 years old.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We found the distribution of TA repeat genotypes was significantly different between cases and controls, but the patterns were not systematic in the overall analysis. In contrast to the two previous studies conducted in African Americans [4] and in Chinese [8], which found that 7 or 8 allele-containing genotypes were associated with elevated risk of breast cancer in premenopausal women [4] or women younger than 40 years [8], we found that these low activity 7 or 8 allele-containing genotypes were associated with decreased risk of breast cancer among premenopausal women or those younger than 45 years old.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have observed that the wild-type allele (UGT1A1*1) was the most common allele among Caucasian, African American and Asian populations [4,6,8,[10][11][12]. We found that the variant allele UGT1A1*28 was as common as UGT1A1*1 allele, with about 40% frequency for each allele among indigenous Africans.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations